(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Canonical bodies in secular system ABSTRACT: This paper considers the different configurations that religious bodies, especially the entities of the Catholic Church, can assume within the civil systems. The extent of the welcoming capacity that States have towards canonical bodies represents a sure indication of the capacity of a juridical order to protect religious freedom and, more generally, the fundamental rights of the person. SOMMARIO: 1. Premessa - 2. Enti canonici e ordinamenti civili - 3. Disciplina canonica e pattizia - 3.1. Il codice del 1983 - 3.2. Il Codice Orientale - 3.3. Concordati e accordi con gli Stati - 4. Rapporti tra persone giuridiche canoniche e civili - 4.1. Il caso delle fondazioni civili - 4.2. La creazione di nuove persone giuridiche civili - 5. L’ente ecclesiastico civilmente riconosciuto in Italia - 5.1. Una soluzione “originale” - 5.2. La rilevanza civile dei controlli canonici - 5.3. Un modello “perfetto”? - 6. Conclusioni.